Os centros de referência em saúde do trabalhador e as ações em saúde mental relacionadas ao trabalho - Cardoso, Mariana de Castro Brandão (2015)
Considering the work as a determining factor in the health / illness physical and mental this study aimed to describe the main actions in mental health related to work in Brazil based on information provided by professionals from the Worker's Health Reference Centers (Cerest) and the following objectives: a) identify the main actions of mental health related to work carried out by state and regional Cerest in the areas of care, occupational health surveillance and health education; b) identify the actions related to health care workers with Mental Disorders Work Related (TMRT) held by Cerest, by regions of Brazil.A survey was conducted with state and regional Cerest implemented in Brazil from October to December 2014 through a questionnaire on –line, 161 Cerest participated. Among statewide response rate was 96.2% and 77.7% among regional. It can be observed that the actions in the area of mental health related to work performed by Cerest occur primarily in the area of assistance, health surveillance of the worker, and TMRT of notification. Overall the actions were carried out mostly by regional Cerest and in the Southeast and Northeast. The actions in mental health is still poor, highlighting the assistance measures for establishing diagnosis and nexus of suspected cases of Mental Disorders Work Related (TMRT) were not being carried out by most of Cerest of Brazil (53.1%), and this case distributed differently by regions of the country. The treatment of mental illnesses related to work was sent to the Caps, but Cerest not followed its evolution. SUS health services are not prepared to receive this demand that has been increasing cases of TMRT. Highlighted the importance of actions in mental health-related work being undertaken by all SUS voltage levels, and inter and intrasectoral actions need to be expanded and strengthened between Cerest and the Health Care Network, especially the Psychosocial Care Network devices to ensuring full attention to these workers. It is necessary to build new research instruments and public policies that help the flow of shares to the ratio of the nexus of the establishment of these diseases with the work in the health services, as well as Occupational Health Surveillance actions in mental health, as illnesses related to work are preventable through improvements in work environments.